Optimizing feed banks as an alternative to animal feed supply in the dry season in Surodadi Village, Magelang - Barkah Susanto; Betari Maharani; Nur Hidayah; Ericka Darmawan; Khalimah Dwi Kurniawati; Nina Ndaru Arlintang; Salsa Hanifatul Fathima; Sukma Auranisha Shifania (Universitas Muhammadiyah Magelang, 2024)
Tepus Wetan Hamlet, Surodadi Village is in close proximity to a 17-hectare pine forest owned by Perhutani, managed by the local community, the majority of whom are engaged in farming and livestock breeding. The dry season poses challenges for farmers in providing feed for their livestock. The objective of this initiative is to enhance feed-making skills, particularly to address dry season challenges. The approach involves raising awareness about the concept and benefits of a Feed Bank, establishing and managing one, and implementing techniques for feed management and storage. Following the awareness campaign, practical training sessions were conducted on Feed Bank setup, management, and utilization. As a result, participants have gained a better understanding of feed banks and acquired new knowledge on sustainable and effective animal feed alternatives during the dry season. This initiative has positively impacted resource efficiency, livestock productivity, and agricultural income.